Digital Literacy Acquisition and Its Application in Face-To-Face Classes in a Private University of Medellin (2023)
This research presents the different stages of digital literacy acquisition (digital tools and skills) that teachers belonging to the English program of a private university in Medellín experienced during the confinement due to the Covid-19 pandemic in the year 2020. It also presents the different challenges that they faced in hybrid education (remote and face-to-face) in 2021, and most importantly, it shows how those teachers are using or not the acquired digital literacy in their face-to-face lessons in the current year 2022. In addition, this research was carried out to help teachers reflect on the importance of the use of digital literacy since their students and society are immersed in technology.